When the State Plays “Philanthropist”: Social Aid as an Instrument of Power Legitimacy - Putra, Muhammad Deni; Rofiki, Akhmad; Argantara, Zaid Raya; Utami, Sari; Addiarrahman, Addiarrahman; Ondri, Dino (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
Social assistance, traditionally regarded as a governmental mechanism for advancing public welfare, frequently extends beyond its humanitarian role in practice and encompasses substantial political implications. Rather than exclusively targeting poverty reduction and inequality mitigation, social assistance is often employed strategically to legitimize and perpetuate state authority. This study critically investigates the reconstruction of social assistance policies as instruments of political domination, wherein the state is portrayed as a “benefactor” whose generosity elicits gratitude and loyalty. Utilizing a qualitative, literature-based methodology, the research identifies recurring patterns of politicization of social assistance across diverse contexts. The findings reveal that political legitimacy is constructed through multiple interconnected mechanisms: the selective allocation of aid serving as political patronage; the internalization of the state’s “savior” narrative via symbolic violence that redefines assistance from a citizen’s entitlement to a discretionary favor; limited political literacy that restricts critical public engagement; and the utilization of aid delivery systems to map, monitor, and consolidate grassroots political support. Consequently, social assistance often becomes a transactional tool fostering clientelistic relationships, undermining democratic participation, and exacerbating social inequality. This study highlights the imperative to reform social assistance governance by emphasizing transparency, accountability, and a rights-based framework, alongside efforts to enhance critical political literacy within society. Abstrak: Bantuan sosial yang secara konvensional dipahami sebagai alat negara untuk mensejahterakan masyarakat, dalam praktiknya sering beroperasi melampaui fungsi kemanusiaan dan menyimpan dimensi politik yang signifikan. Alih-alih semata ditujukan untuk pengentasan kemiskinan dan pengurangan ketimpangan, bantuan sosial kerap diposisikan sebagai instrumen strategis untuk melegitimasi dan mempertahankan kekuasaan negara. Penelitian ini bertujuan menelaah secara kritis bagaimana kebijakan bantuan sosial direkonstruksi untuk menopang dominasi politik dengan membingkai negara sebagai “dermawan” yang kebaikannya menuntut rasa syukur dan loyalitas. Menggunakan metode kualitatif berbasis studi literatur, penelitian ini mengidentifikasi pola politisasi bantuan sosial dalam berbagai konteks. Temuan menunjukkan bahwa legitimasi kekuasaan dibangun melalui beberapa mekanisme yang saling terkait: distribusi bantuan yang selektif sebagai sistem imbalan politik; internalisasi narasi negara sebagai “penyelamat” melalui kekerasan simbolik yang menggeser makna bantuan dari hak warga menjadi pemberian; rendahnya literasi politik yang membatasi kesadaran kritis masyarakat; serta pemanfaatan infrastruktur bantuan untuk memetakan dan mengonsolidasikan dukungan politik di tingkat akar rumput. Akibatnya, bantuan sosial cenderung berubah menjadi instrumen transaksional yang memproduksi relasi klientelistik, melemahkan partisipasi demokratis, dan memperdalam ketimpangan sosial. Studi ini menegaskan urgensi reformasi tata kelola bantuan sosial berbasis transparansi, akuntabilitas, dan pendekatan berbasis hak, disertai penguatan literasi politik kritis masyarakat.